The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/la901789h
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-Tuned Preparation of Nanoliposomes

Abstract: Numerous methods have been reported for the preparation of liposomes, many of which, in addition to requiring time-consuming preparative steps and the use of organic solvents, result in heterogeneous liposome populations of incontrollable size. Taking into consideration the phenomenon of spontaneous vesiculation and the theory of curvature, here we present an extremely rapid and simple, solvent-free method for the preparation of monodisperse solutions of highly stable small unilamellar vesicles using both char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…16,21 The giant micelles-to-vesicle transition observed in the G-C18:1 sample is undoubtedly explained by the presence of the less bulky glucose headgroup, with respect to the sophorose disaccharide. The fact that this compound has the same oleic acid moiety as SL-C18:1 is a good hint of the fact that the headgroup plays the most important role in driving the formation of micelles, or vesicles.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…16,21 The giant micelles-to-vesicle transition observed in the G-C18:1 sample is undoubtedly explained by the presence of the less bulky glucose headgroup, with respect to the sophorose disaccharide. The fact that this compound has the same oleic acid moiety as SL-C18:1 is a good hint of the fact that the headgroup plays the most important role in driving the formation of micelles, or vesicles.…”
Section: Discussionmentioning
confidence: 98%
“…Small Angle X-ray Scattering (SAXS): several publications have shown that the stimuli-driven self-assembly of lipids is a non-equilibrium process; 16,17 for this reason, we have repeated SAXS experiments on three different instruments using both ex-situ and in-situ analyses, one being complementary to the other. In the ex-situ approach, the self-assembled structures are analyzed within a few hours after their preparation.…”
Section: Light Scattering (Ls)mentioning
confidence: 99%
See 3 more Smart Citations